O Ensino dos jogos sociomotrizes de cooperação nas aulas de Educação Física e suas influências nas condutas motrizes dos alunos - Vasconcelos, Yorahina Ariadne [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
O desenvolvimento de jogos foi se constituindo, ao longo do tempo, como um conhecimento no ensino da Educação Física, portanto, eles podem contribuir e estabelecer determinadas condutas motrizes entre os estudantes. Todavia, ainda pouco sabemos sobre a relação entre as estruturas dos jogos com as condutas construídas pelos estudantes. Entendemos, ancoradas na teoria da Praxiologia Motriz, que a conduta motriz estabelece aproximação com o comportamento motor carregado de significado, não sendo uma ação essencialmente corporal e padronizada, destituída dos aspectos afetivos, cognitivos e socioculturais. Com base nessa consideração, este estudo teve como objetivo identificar e analisar as condutas motrizes dos alunos de uma turma de 2º ano do ensino fundamental no interior dos jogos sociomotrizes de cooperação nas aulas de Educação Física, aproximando assim as teorias da Praxiologia Motriz e da Educação Física. A pesquisa foi fundamentada na abordagem qualitativa, balizando-se por uma pesquisa-intervenção, realizada nas aulas de Educação Física. A utilização dos jogos sociomotrizes de cooperação possibilitou, gradativamente, o desenvolvimento da conscientização dos estudantes sobre a lógica interna, bem como, o reconhecimento das condutas motrizes apresentadas durante a vivência dos jogos. implementação de jogos sociomotrizes de cooperação em uma abordagem de ensino nas aulas de Educação Física demonstrou ser uma experiência que otimizou as condutas motrizes, influenciando diretamente nas competências sociais dos estudantes e na construção de vivências socioemocionais positivas.

The development of games has become, over time, a form of knowledge in the teaching of Physical Education, therefore, they can contribute and establish certain behaviors among students. However, we still know little about the relationship between the structures of games and the behaviors constructed by students. We understand, anchored in the theory of Motor Praxiology, that motor behavior is close to motor behavior loaded with meaning, not being an essentially corporal and standardized action, devoid of affective, cognitive and sociocultural aspects. Based on this consideration, this study aimed to identify and analyze the motor conduct of students in a 2nd year elementary school class within sociomotive cooperation games in Physical Education classes, thus bringing together the theories of Motor Praxiology and Education Physical. The research was based on a qualitative approach, guided by an intervention research, carried out in Physical Education classes with the participation of 21 students aged seven to eight years old from a 2nd year elementary school class. The subjects totaled 15 classes of 55 minutes each and the collection instruments used were: 1. Conversation circles; 2. Class diaries; 3. Interview; 4. Class observation. The results highlighted three categories of analysis, namely: 1. The motor conduct of students within sociomotive cooperation games; 2. Space, rhythm, participants, materials and rules in sociomotive cooperation games; 3. Sociomotive games ofcooperation and emotions between students. The use of cooperation sociomotive games gradually enabled the development of students' awareness of internal logic, as well as the recognition of the motor conduct presented during the experience of the games. This process became possible through pedagogical mediations, mobilized by the teacher-researcher, in which students were able to share individually and collectively their experiences. The implementation of cooperative sociomotive games in a teaching approach in Physical Education classes proved to be an experience that optimized motor conduct, directly influencing students' social skills and the construction of positive socioemotional experiences. The use of sociomotive cooperation games gradually made it possible to raise students' awareness of internal logic and mainly consider the motor conduct presented during the experience of these games. This process became possible through pedagogical mediations in which students were able to share experiences lived individually and collectively. The implementation of cooperative sociomotive games in a teaching approach in Physical Education classes proved to be a positive experience in terms of optimizing motor conduct, directly influencing students' social skills and the intrinsic recognition of cooperative motor situations as socio-emotional experiences positive.
Teaching sociomotive cooperation games in Physical Education classes and their influence on students’ motor behaviors
Keywords: Praxiologia motriz; Educação Física; Conduta motriz; Motor praxiology; Physical education; Motor conduct